Covenant-light contracts and creditor coordination - Bo Becker; Victoria Ivashina (Sveriges Riksbank, 2016)
In 2015, 70% of newly-issued leveraged loans had weaker enforcement features, called covenant-light or "cov-lite;" this is nearly a three-time increase in cov-lite issuance compared to a previous peak in 2007. We evaluate whether this development can be attributed to market overheating, increased borrower demand for cov-lite loans, or a rise in creditor coordination costs. The last hypothesis stems from the increasing involvement of non-bank institutions and, in particular, the rise of mutual fund participation in the leveraged loan market after the financial crisis. Based on the wider syndication, (narrower) skills, and diverse incentives of non-bank institutional lenders, optimal contracts between them and corporate borrowers likely involve fewer monitoring tools and weaker control rights. We evaluate these explanations of cov-lite contract provisions in a large sample of U.S. loans for the 2001-2014 period. Consistent with creditor-driven explanations for cov-lite issuance, we show that cov-lite prices compress as the prevalence of cov-lite rises. Time patterns in cov-lite issuance closely match inflows to institutional lenders, and at a given time, cov-lite loans are, overwhelmingly, those with the highest ownership by structured products and/or mutual funds. The number and share of structured products and mutual funds also impact the propensity toward other contractual features that influence when and how creditors have control. However, these factors are less relevant in explaining the strength of restrictions on indebtedness, liens, payments, or assets sales.
Keywords: G11; G22; G30; 330; Credit cycles; Loan contracts; Debt Covenants